2013
DOI: 10.1177/1933719113488444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drospirenone–Ethinylestradiol and/or Metformin on CD4+CD28null T Lymphocytes Frequency in Women With Hyperinsulinemia Having Polycystic Ovary Syndrome: A Randomized Clinical Trial

Abstract: In women with hyperinsulinemic PCOS, combined therapy with DRSP/EE and metformin may reduce cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
13
0
1
Order By: Relevance
“…IL-17 and IFN-γ levels were higher in patients with poor glucoregulation at baseline (defined as a glycated hemoglobin >7%); nonetheless, a 12-week treatment with metformin could reduce IL-17 in diabetic patients. Finally, in patients with polycystic ovary syndrome (PCOS), the administration of metformin combined with drospirenone/ethinylestradiol has been shown to reduce the frequency of CD4 + CD28 null T cells ( 51 ), a subset of CD4 + Th1 cells lacking the co-stimulatory receptor CD28 thought to be involved in autoimmune diseases such as RA ( 52 ).…”
Section: Effects Of Metformin On Immune Cells Involved In Autoimmune mentioning
confidence: 99%
“…IL-17 and IFN-γ levels were higher in patients with poor glucoregulation at baseline (defined as a glycated hemoglobin >7%); nonetheless, a 12-week treatment with metformin could reduce IL-17 in diabetic patients. Finally, in patients with polycystic ovary syndrome (PCOS), the administration of metformin combined with drospirenone/ethinylestradiol has been shown to reduce the frequency of CD4 + CD28 null T cells ( 51 ), a subset of CD4 + Th1 cells lacking the co-stimulatory receptor CD28 thought to be involved in autoimmune diseases such as RA ( 52 ).…”
Section: Effects Of Metformin On Immune Cells Involved In Autoimmune mentioning
confidence: 99%
“…To this regard, the effects of different therapeutic regimens on CD4 + CD28 − T cell frequencies have been investigated in patients with hyperinsulinemic polycystic ovary syndrome, in which increased frequencies of this subset have also been observed (but an association with CMV has not been investigated). Treatment with drospirenone–ethinylestradiol and metformin resulted in a significant reduction of frequencies of CD4 + CD28 − T cells ( 88 ). Moreover, it has been demonstrated in organ transplant recipients that treatment with polyclonal anti-thymocyte globulin preferentially triggers apoptosis in CD4 + CD28 − compared to CD4 + CD28 + T cells ( 89 ).…”
Section: Could Cd4 + Cd28 − T Cmentioning
confidence: 99%
“…In PCOS patients with no reproductive requirements, the long-term use of COCs have shown to increase the risk of venous thrombosis. However, none of the study patients reported venous thromboembolism (VTE) but milder ADRs that included breast tenderness/swelling along with headache and dizziness as reported elsewhere [32]. The degree of cycle control was also effective with majority of women having normal menstruation at follow up ( Table 2).…”
Section: Discussionmentioning
confidence: 83%